Chronic Opioid Therapy in People Living With Human Immunodeficiency Virus: Patients' Perspectives on Risks, Monitoring, and Guidelines. (31st May 2018) - Colasanti, Jonathan; Lira, Marlene C; Cheng, Debbie M; Liebschutz, Jane M; Tsui, Judith I; Forman, Leah S; Sullivan, Meg; Walley, Alexander Y; Bridden, Carly; Root, Christin; Podolsky, Melissa; Abrams, Catherine; et al.
Abstract : Among people living with HIV on chronic opioid therapy, few report receiving guideline concordant monitoring practices. Among those receiving monitoring, high satisfaction was reported. Risk of opioid misuse was not associated with receiving monitoring practice nor satisfaction with that monitoring. Abstract: Background: Chronic opioid therapy (COT) is common in people living with human immunodeficiency virus (PLHIV), but is not well studied. We assessed opioid risk behaviors, perceptions of risk, opioid monitoring, and associated Current Opioid Misuse Measure (COMM) scores of PLHIV on COT. Methods: COT was defined as ≥3 opioid prescriptions ≥21 days apart in the past 6 months. Demographics, substance use, COMM score, and perceptions of and satisfaction with COT monitoring were assessed among PLHIV on COT from 2 HIV clinics. Results: Among participants (N = 165) on COT, 66% were male and 72% were black, with a median age of 55 (standard deviation, 8) years. Alcohol and drug use disorders were present in 17% and 19%, respectively. In 43%, the COMM score, a measure of potential opioid misuse, was high. Thirty percent had an opioid treatment agreement, 66% a urine drug test (UDT), and 12% a pill count. Ninety percent acknowledged opioids' addictive potential. Median (interquartile range) satisfaction levels (1–10 [10 = highest]) were 10 (7–10) for opioid treatment agreements, 9.5 (6–10) for pill counts, and 10 (8–10) for UDT. No association was found between higher COMM score and receipt of or satisfaction with COT monitoring. Conclusions: Among PLHIV on COT, opioid misuse and awareness of the addictive potential of COT are common, yet COT monitoring practices were not guideline concordant. Patients who received monitoring practices reported high satisfaction. Patient attitudes suggest high acceptance of guideline concordant care for PLHIV on COT when it occurs.